Surveying Vocational Rehabilitation Applicants Online: A Feasibility Study. (December 2019) - Chandler, Jesse J.
Web surveys enable efficient data collection, but their usefulness is potentially limited when studying people with disabilities, who often lack Internet access. We test the feasibility of collecting web survey data from a sample of state vocational rehabilitation (VR) applicants, inviting nonrespondents to complete a telephone interview instead. People who lacked Internet access were provided with a mobile device and wireless access and were as likely to complete the web surveys as people who already had Internet access. Respondents who elected to complete the survey online versus by telephone differed in level of education and VR experience. These findings suggest that for disability studies, web surveys are an important supplement to, but not a replacement for, traditional data collection efforts.